D‐mannose alleviated alveolar bone loss in mice with experimental periodontitis via regulating the anti‐inflammatory effect of amino acids. Issue 4 (9th November 2022) - Yang, Hua; Han, Nannan; Luo, Zhenhua; Xu, Junji; Guo, Lijia; Liu, Yi
Abstract: Background: Periodontitis is a chronic infectious disease caused by dysbiosis of oral microbiota, ultimately leading to periodontal alveolar bone loss. The oral subgingival microbiome, a key role in periodontitis pathogenesis, could alter the composition of gut microbiomes resulting in intestinal microbiota disorder. D‐mannose plays an important role in glucose metabolism; whether it is beneficial to prevention and treatment of periodontitis and the regulation of oral and intestinal microbiota changes is still unknown. Methods: To explore the effect of D‐mannose, we established experimental periodontitis models in mice and then treated with supplementation of D‐mannose in drinking water or gavage to examine the extent of periodontal bone loss using methylene blue staining. Moreover, the oral and fecal samples of mice were collected for 16S rRNA deep sequencing to analyze the changes of oral and gut microbiota after 14 days. Furthermore, amino acid content assays were used to test the concentration of amino acid of gingival tissues and intestinal tissues. Results: We found that D‐mannose could alleviate periodontal bone loss whether in the manner of drinking water or gavage. 16S rRNA results revealed that the abundance of Firmicutes changed significantly in oral samples, while Firmicutes and Akkermansia muciniphila were dominated in gut microbiota. In addition, we demonstrated that D‐mannose inhibited inflammation and alleviated alveolar bone loss in periodontitis via regulating amino acid metabolism of oral and gut microbiomes. Conclusion: Our findings provided insight into the mechanism underlying the abilities of D‐mannose in improving periodontitis treatment, suggesting that D‐mannose has potential application in the dental clinic.